Assessment of the level of knowledge of women the risk factors Osteoporosis and its application in practice - Paplaczyk, Małgorzata; Gawor, Anna; Palka, Aleksandra; Chrobak-Bien, Joanna (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction: Osteoporosis is characterized by loss in bone weight, which leads to often fractures. The disease is one of the main health problems in Poland. The progression of the disease is contributed by many factors, like age, sex, inappropriate diet, low physical activity, smoking and lack of health prevention and education. The purpose of thesis: The purpose of the research was to check the level of women's knowlege on the osteoporosis risk factors and health actions taken. Resources and methods: The research was carried out on 105 women at the age of 40 – 76. The method used was diagnostic survey, with the following tools: author's questionnaire of survey and Inventory of Health Behaviours. Results: Less than 50% of women shown very good level of knowledge, basing on author's questionnaire of survey, and over 50% of women characterized with the average level of health behaviours. The harmful results of smoking are mostly noticed by women who quit smoking, and in the least by those who smoke more than one packet per day. Conclusions: The analysis of the results of the research leads to the statement, that the knowlege on osteoporosis risk factors is insuficient. The results show the need for running education on osteoporosis prevention and for promotion of health behaviors both of health and sick people, to prevent the sickness and to eliminate the factors that enhance the sickness.